KRIPTOGRAFI HYBRIDA MENGGUNAKAN ALGORITMA HILL CIPHER DAN ALGORITMA RSA UNTUK KEAMANAN PENGIRIMAN INFORMASI PADA EMAIL - Lisda Juliana Pangaribuan; Fauzi Haris Simbolon (STMIK Budi Darma, 2017)
This research aims to analyze the performance of the algorithm that can improve the security message with a hybrid cryptosystem using algorithm hill cipher and RSA asymmetric key with a key so that the size of file after the encrypted small time for process encryption and decryption fast. The algorithm used is a modification algorithms Hill Cipher. This research uses hybrid cryptosystem, which message is hidden by using hill cipher and the key is hidden by using RSA algorithm. The results of this research is that a better message security by making the hybrid cryptosystem using fingerprint image of sender as a key that will be secured because the encryption key is not equal tothe decryption key. Besides it is very difficult to guess the key figures for the sum of characters that is sent to the recipient's key is not equal to the actual number of key characters. The time is used to decrypt the ciphertext with hybrid hill cipher and RSA algorithm for the number of characters and fingerprint image with the same threshold value turned out to be longer than the time that is used to decrypt the cipher text with hill cipher algorithm. The sum of characters (size of file) after encrypted and decrypted same. This is because the use of modulo 256 in the calculation of the encryption so the limit of character after encrypted and decrypted between 0 to 255. Each character encrypted will be 1 ASCII character as well.